Case Report: Culture-Dependent Postures in Japanese Patients With Schizophrenia - Koreki, Akihiro; Koizumi, Teruki; Ogyu, Kamiyu; Onaya, Mitsumoto (Frontiers in Psychiatry, 2021)
Lack of knowledge regarding culture-dependent behaviours may lead to misjudgement by clinicians, resulting in inappropriate treatment. Therefore, cross-cultural understanding of psychiatric symptoms is important in today’s globalised society. In the present case report, we report on two patients with schizophrenia who showed these Japanese-culture-dependent postures (seiza and dogeza). Seiza is a Japanese style of formal floor sitting. Dogeza includes bowing and toughing the forehead to the floor while sitting in a kneeling position. Performance of these postures by patients with schizophrenia in the clinical setting provides clinicians with plenty of information regarding the patients’ clinical states, such as schizophrenia-related fear/tension, accusatory auditory verbal hallucinations and pathological guilty.